Prospective study of predictors of poor self-rated health in a 23-year cohort of earthquake survivors in Armenia - Anahit Demirchyan; Varduhi Petrosyan; Haroutune K. Armenian; Vahe Khachadourian (Springer, 2019)
Long-term prospective studies exploring general health outcomes among disaster survivors are rare. Self-rated health (SRH) - a proven correlate of morbidity and mortality prognosis - was used to investigate predictors of perceived health status among a 23-year cohort of survivors of 1988 Spitak earthquake in Armenia. A geographically-stratified subsample of 725 adults from a larger initial cohort was followed during the period of 1990-2012. A logistic regression model identified predictors of SRH. Adjusted relative risks for the long-term predictors of SRH were calculated. The rate of poor SRH among the survivors was 18.8%, fair 56.5%, and good/excellent 24.7%. In the fitted model, long-term risk factors of poor SRH included baseline body mass index, baseline multi-morbidity, number of experienced stressful life events, and perceived poor living standards during the post-earthquake decade, while participation in sports in the early 1990s was a protective factor. Short-term protective factors included socio-economic status score, social support, employment and dignity, while current household size was a risk factor for poor SRH. No association was found between earthquake exposure severity and SRH after 23 years. However, the identified predictors included a number of modifiable lifestyle, material and psychological factors. Thus, interventions targeting these factors could have a long-lasting impact on disaster victims' health status.